Rethinking disaster risk for ecological risk assessment - Singh, Gerald G.; Sajid, Zaman; Khan, Faisal; Mather, Charles; Bernhardt, Joey R.; Frölicher, Thomas L. (Frontiers in Ecology and Evolution, 2023)
While disaster events are consequential, they are rare. Technical ecological risk assessment processes tend to estimate risk through an "expected value" lens that focuses on the most probable events, which can drastically underappreciate the importance of rare events. Here, we show that expected value and average risk-based calculations underappreciate disaster events through questionable assumptions about equally weighing high probability low impact events with low probability high impact events, and in modeling probability as a chance among an ensemble of possible futures when many contexts of ecological risk assessment are focused on a single entity over time. We propose an update to ecological risk assessment that is specifically inclusive of disaster risk potential by adopting analytical processes that estimate the maximum hazard or impact that might be experienced in the future, borrowing from the practice of modeling "Value at Risk" in financial risk contexts. We show how this approach can be adopted in a variety of data contexts, including situations where no quantitative data is available and risk assessment is based on expert judgement, which is common for ecological risk assessment. Increased exposure to environmental variation requires assessment tools to better prepare for, mitigate, and respond to disasters.Introduction Many environmental and development disasters such as floods, oil spills, droughts, heatwaves,